Simultaneous Occurrence of Herpes Zoster and Chickenpox in a Patient - A Case Report - Saha, Suranjit Kumar; Islam, M M Shahin Ul; Yousuf Zaki, Md Hasnat; Uddin, Md Nizam; Saha, Prativa (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Varicella zoster virus (VZV) infection primarily causes varicella or chickenpox. Herpes zoster (HZ) or shingles is the manifestation due to reactivation of same virus. Simultaneous occurrence of HZ and Chickenpox in a patient is an uncommon event. A 14 years old apparently healthy girl came to the medicine outpatient department of Pirojpur District Hospital with the complaints of burning pain in the right side of forehead followed by maculopapular rash and blister lesion with painful right red eye. The lesions were anatomically distributed along the dermatome of right sided ophthalmic division of trigeminal nerve. Simultaneously she developed some small vesicular lesion in her trunk. At that time she had fever, bodyache and malaise. The entire lesion was healed with crusting within seven to ten days. She had no significant past history. With a course of antiviral and symptomatic treatment, she recovered without any complication. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(1):03-07